Student’s misconception of digestive system materials in MTs eight grade of Malang city and the role of teacher’s pedadogic competency in MTs - Yuswa Istikomayanti; Zuni Mitasari (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
Misconception research has important value in the development of students' thinking processes especially in science field. As the identification of important concepts that must be mastered by the students can be done, the teacher will easily able to emphasis the important or main concepts. This study aims to identify the students’ misconception in digestive system materials in eight grade of MTs and teacher pedagogic competence role. The survey was conducted in 8A (16 students) and 8B (17 students) MTs Muhammadiyah 1 and 8E (19 students) Surya Buana Malang. The stages of research survey were: preparation of research goals (formulation), sample determination, preparation and instruments validation, data collection, and data analysis. The instruments used were: misconception test, student response questionnaire, learning observation guide, and teacher pedagogic competency form. The findings of the learning outcomes were discussed with the observer team, which then were assessed by using the assessment rubric and classified into the categories of student misconceptions. The results showed that the three teachers, neither certified nor uncertified were proved to be limited in overcoming misconceptions in the learning process; meanwhile, the results of students’ misconception test were mostly reach only level 3 (medium). Thus, the study of misconceptions of the digestive system material or other physiological material matter needs to get the attention of the teachers and educational practitioners.